Propane Dehydrogenation over In2O3–Ga2O3–Al2O3 Mixed Oxides. Issue 1 (3rd November 2015) - Tan, Shuai; Kim, Seok‐Jhin; Moore, Jason S.; Liu, Yujun; Dixit, Ravindra S.; Pendergast, John G.; Sholl, David S.; Nair, Sankar; Jones, Christopher W.
Abstract: A series of ternary mixed metal oxides containing Group III A elements (In, Ga, Al) is prepared by means of an alcoholic co‐precipitation method. Specifically, oxide catalysts with a molar composition of In/Ga/Al=5:15:80, 10:10:80, and 15:5:80 are reported. The chemical composition, redox properties, and catalyst structures are fully characterized, with the results suggesting that the indium, gallium, and aluminum moieties are well‐dispersed in the catalysts. The catalysts are evaluated for propane dehydrogenation (PDH) at 570 and 600 °C under 1 atm total pressure. The most effective catalyst with a composition of In/Ga/Al=5:15:80 provides 17 % conversion and approximately 86 % C3 H6 selectivity with an initial activity of 4.6 mmol h −1  gcat −1 and 24.1 μmol h −1  m −2 . The intrinsic activity on an active metal (i.e. indium and gallium) basis is approximately 3 times that of the In2 O3 –Ga2 O3 family and approximately 3–9 times that of the In2 O3 –Al2 O3 family. The catalyst deactivates with time on stream, and regeneration tests show that removal of surface coke and recovery of an In2 O3 state helps to regain the initial activity, whereas reducing In2 O3 domains into In 0 does not allow for recovery of the performance. Raman analysis of the carbonaceous species deposited on the catalyst indicates catalysts with higher gallium content give more graphitic carbon, which correlates with higher C3 H6 selectivity, whereas catalysts with more disordered coke are associated with lower selectivity. However, higher gallium content causes more coke formation, which leads to faster deactivation. This initial study of this family of mixed oxides suggests that an ideal In/Ga ratio may exist whereby catalyst properties may be optimized. Abstract : Mixing it up : Mixed indium–gallium–aluminum oxides are prepared and characterized as precious metal‐free propane dehydrogenation catalysts.